Cuban international relations at 60 reflections on global connections - Bain, Mervyn J., 1973-; Walker, Chris, 1981- (Lexington studies on Cuba., 2021)
"While scrutinizing the principle pressures and influences of Cuba's key international relationships and issues, Cuban International Relations at 60 examines the island's global engagement and foreign policy since January 1959 by bringing together the perspectives of leading experts and personal accounts of two ambassadors"--